Controversies in monitoring metastatic breast cancer during systemic treatment. Results of a GIM (Gruppo Italiano Mammella) survey. (August 2018) - Bonotto, Marta; Basile, Debora; Gerratana, Lorenzo; Pelizzari, Giacomo; Bartoletti, Michele; Vitale, Maria Grazia; Fanotto, Valentina; Lisanti, Camilla; Mansutti, Mauro; Minisini, Alessandro Marco; Aprile, Giuseppe; De Laurentiis, Michele; et al.
Abstract: Background: The optimal strategy for monitoring metastatic breast cancer (M-MBC) is unclear. Nevertheless, M-MBC influences patient's quality of life and it affects the use of resources in terms of both drugs and diagnostic exam prescription. We aim to disclose oncologists' approach on M-MBC, identifying controversial areas. Methods: An anonymous online survey was conducted among GIM members who, based on their on-field experience, shared their own method for M-MBC planning. Chi-square tests and Fisher exact tests were used as appropriate. Results: The survey was completed by 256 recipients (51%). The majority of them were medical oncologists. Approximately 50% of respondents reported that M-MBC was primarily based on the monitoring strategies used in clinical trials, and for 70% of them M-MBC should be evidence-based. Areas of controversies included the primary goal of M-MBC, the use of tumour markers, the optimal timing for baseline assessment and frequency of repeating testing. Respondents agreed on planning M-MBC before treatment's start and on discussing with the patient about the M-MBC strategy and on choosing CT-scan as the preferred reassessment imaging method. The most relevant factors influencing the M-MBC strategy were performance status, triple negative histology, exam's contraindication, the presence of clinically measurable disease, and treatment safety profile; on the contrary, patients' socio-economic status, exam's cost, and hospital's logistic limits were less relevant. Experienced oncologists seemed less prone to intensive follow-up. Conclusion: M-MBC strategy still has controversial issues and its potential clinical effects for breast cancer patients need ad hoc studies. Highlights: Narrow guidelines for metastatic breast cancer monitoring are not yet available. Disease monitoring impacts on use of resources. Frequent monitoring is associated with emotional harms, despite unclear benefits. Oncologists with more experience seemed less prone to intensive follow-up. Oncologists call for literature data on the matter.